Integrating Maqāṣid al-Sharī‘ah into the Legal Framework of Child Adoption in Indonesia - Muhammad Alifza; Nasution, Muhammad Amin (Al-Risalah, 2025)
This study aims to analyze the alignment of child adoption regulations in the Child Protection Law and its implementing regulations with the principles of maqāṣid al-sharī‘ah, particularly in relation to ḥifẓ al-nafs (protection of life) and ḥifẓ al-naṣl (protection of lineage). The widespread practice of informal child adoption without court authorization—especially in rural areas—raises legal concerns regarding lineage, identity, and the rights of child protection from both positive legal and Islamic perspectives. This research employs a normative-juridical method with a statutory and Islamic jurisprudence approach, supported by secondary data obtained from a field study in Beji Village, Banyumas. The analysis uses al-Ghazālī’s maqāṣid al-sharī‘ah framework to assess the compatibility between existing regulations and Islamic values on child protection. The findings indicate that the national legal framework essentially accommodates the principles of safeguarding life and lineage; however, there remain implementation gaps due to limited legal literacy, the influence of local traditions, and economic factors. The study’s original contribution lies in its proposal of a “structured kafālah” model as an integrative approach combining positive law and Islamic law, along with a recommendation for Islamic-based legal training for village officials and communities. The implication is that strengthening regulations and education that integrate maqāṣid al-sharī‘ah into adoption practices is crucial to ensure lawful, just, and contextually relevant child protection in accordance with both legal and religious values.